P-CoPt3 / P-CoMoO4 heterostructure hydrogen evolution electrocatalyst as well as preparation method and application thereof
By in situ generating P-CoPt3/P-CoMoO4 heterostructure hydrogen evolution electrocatalyst on the P-CoMoO4 nanorod array, the problems of low HER activity and scarce precious metal platinum resources in alkaline environments are solved, and efficient and stable electrolyzed hydrogen production is achieved, reducing production costs.
Patent Information
- Application Number
- CN202510086859.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The prior art has low activity in an alkaline environment and the scarce resources of precious metal platinum, resulting in high cost of electrolyzing hydrogen production, which limits the application of hydrogen energy.
The solution immersion method was used to generate P-CoPt3/P-CoMoO4 heterostructure hydrogen evolution electrocatalyst on the P-CoPt3/P-CoMoO4 heterostructure hydrogen evolution electrocatalyst by a solution immersion method. The hydrogen evolution electrocatalyst was formed by anchoring the three-dimensional open nanorod array through phosphorus-doped CoPt3 to form a stable heterostructure, improving catalytic activity and stability.
Under the premise of low Pt loading, P-CoPt3/P-CoMoO4 heterostructure hydrogen evolution electrocatalyst exhibits intrinsic catalytic activity and long-term stability that is better than most platinum-based materials, and is suitable for hydrogen production under industrial-grade high current density.
Smart Images

Figure CN119956419A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts, and in particular relates to a P-CoPt3 / P-CoMoO4 heterostructure hydrogen evolution electrocatalyst and a preparation method and application thereof. Background Art
[0002] With the development of economy, the global demand for energy is increasing, and the limited fossil energy will be exhausted one day. Moreover, the use of fossil fuels is accompanied by the production of greenhouse gases such as carbon dioxide, which aggravates the problem of global warming. The development of clean new energy to replace traditional fossil energy has become a top priority for social development. Hydrogen energy is considered to be an ideal energy carrier because of its advantages such as cleanliness, pollution-free and wide access. Hydrogen, as a sustainable, environmentally friendly and high energy density energy carrier, has attracted widespread attention. Compared with traditional fossil energy hydrogen production, electrocatalytic water splitting hydrogen production shows greater advantages. The development of excellent electrocatalytic hydrogen evolution (HER) catalysts plays a vital role in the development and utilization of renewable energy.
[0003] In alkaline environments, the activity of the hydrogen evolution reaction (HER) is usually low because of the high water dissociation barrier in the Volmer step. Therefore, the development of HER catalysts with high activity under alkaline conditions to efficiently produce hydrogen has become an important research topic. According to the classic volcano plot theory, noble metals such as platinum and their derivatives have ideal hydrogen adsorption / desorption Gibbs free energy, but due to the scarcity and high price of platinum resources, the cost of hydrogen production by electrolysis of water is high, which limits the widespread application of hydrogen energy. Therefore, alloying is often used to reduce the content of precious metal platinum and improve its activity and stability. However, platinum-based metal alloys Pt-M (M = Co, Ni, Fe and other transition metals) binary alloys show high activity for HER by adjusting the local coordination environment of Pt. However, the instability of Pt-M alloys due to the dissolution of M limits their further practical application. Heteroatom dopants (P, S) can alleviate the dissolution problem of M to a certain extent, but unfortunately, the HER catalytic activity of the obtained doped Pt-M alloys is not ideal. Therefore, improving the catalytic efficiency and stability of Pt-M alloys has attracted much attention.
[0004] At the same time, the current density of industrial applications is usually 500mAcm -2Above the current density of , under such high current density conditions, it will lead to the transition dissolution and shedding of the catalyst. Heterointerface engineering is widely regarded as a promising method to improve catalytic activity, in which the heterointerface regulates the fine structure of the catalyst, produces new and more active catalytic sites on the heterointerface, and thus greatly improves the catalytic activity. Therefore, how to reduce the content of precious metal platinum and improve the stability of platinum-based alloy catalysts. The current effective strategy is to combine it with a self-supporting carrier to form a heterostructure, thereby improving the intrinsic activity and intrinsic stability of the catalyst, especially under industrial-grade current density conditions. Existing methods for achieving heterostructure modification usually include electrodeposition, hydrothermal and atomic layer deposition, but these methods all require additional energy consumption, and there are problems such as complex process flow and low efficiency. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a P-CoPt3 / P-CoMoO4 heterostructure hydrogen evolution electrocatalyst and its preparation method and application, wherein the hydrogen evolution electrocatalyst has extremely low overpotential and good stability, and the preparation process is simple and efficient, and can be applied to hydrogen evolution by electrolysis of water under industrial-grade high current density.
[0006] The inventive concept of the present invention is: the present invention adopts a simple and controllable solution immersion method to generate a P-CoPt3 / P-CoMoO4 heterostructure hydrogen evolution electrocatalyst by in-situ spontaneous redox reaction on a P-CoMoO4 nanorod array. The hydrogen evolution electrocatalyst first synthesizes CoMoO4 nanorod arrays by a hydrothermal method, and then obtains self-supporting phosphorus-doped CoMoO4 nanorod arrays (P-CoMoO4) by a high-temperature phosphating process. The P-CoMoO4 nanorod structure is conducive to the transmission of large currents. The P-CoMoO4 nanorod arrays are then immersed in a solution containing platinum ions, and a redox reaction occurs spontaneously at room temperature to obtain phosphorus-doped CoPt3 (P-CoPt3). P-CoPt3 is anchored on the three-dimensional open nanorod array P-CoMoO4, which can not only avoid the transition aggregation of P-CoPt3 and thus affect the exposure and utilization of catalytic active sites, but also the strong interaction between P-CoPt3 and the carrier P-CoMoO4 can effectively inhibit the dissolution of transition metal cobalt in CoPt3, and can avoid P-CoPt3 from falling off the carrier at high current density, thereby greatly improving the activity and long-term stability of the catalyst. Therefore, the P-CoPt3 / P-CoMoO4 heterostructure nanorod array hydrogen evolution electrocatalyst prepared by the present invention has an intrinsic catalytic activity and long-term stability superior to most platinum-based materials under the premise of low Pt loading, and has good application prospects under industrial-grade high current density.
[0007] To solve the above technical problems, the first aspect of the present invention provides a hydrogen evolution electrocatalyst, comprising a nickel foam substrate and a catalytically active material loaded on the surface of the nickel foam substrate, the catalytically active material comprising phosphorus-doped CoMoO4 and phosphorus-doped CoPt3, the phosphorus-doped CoMoO4 having a three-dimensional open nanorod array structure, the phosphorus-doped CoPt3 being anchored on the nanorod array, and the phosphorus-doped CoMoO4 and phosphorus-doped CoPt3 forming a heterostructure.
[0008] In some embodiments of the present invention, in the hydrogen evolution electrocatalyst, the loading amount of the catalytically active material is 9-10 mg / cm 2 .
[0009] In some embodiments of the present invention, in the catalytically active material, the content of Pt is 5-15wt%, the content of Mo is 30-40wt%, the content of Co is 15-25wt%, and the content of P is 1-5wt%. In the catalytically active material of the present invention, the content of the noble metal Pt is low, which can greatly save production costs.
[0010] In some embodiments of the present invention, in the catalytically active material, the content of Pt is 7-13 wt%, the content of Mo is 33-36 wt%, the content of Co is 20-23 wt%, and the content of P is 2-3 wt%.
[0011] The second aspect of the present invention provides a method for preparing the above-mentioned hydrogen evolution electrocatalyst, comprising the following steps:
[0012] (1) immersing the nickel foam in a mixed solution containing molybdate and cobalt salt to perform a hydrothermal reaction, and then washing and drying to obtain cobalt molybdate grown on the surface of the nickel foam;
[0013] (2) placing the nickel foam with cobalt molybdate grown on the surface obtained in step (1) and a phosphorus source at the downstream and upstream of the airflow in the reaction furnace respectively, heating them to carry out a phosphating reaction, and obtaining a phosphorus-doped cobalt molybdate nanoarray, which is recorded as P-CoMoO4;
[0014] (3) The P-CoMoO4 is immersed in a solution containing platinum ions, and a redox reaction is carried out at room temperature to generate P-CoPt3 in situ on the surface of P-CoMoO4. After washing and drying, the hydrogen evolution electrocatalyst is obtained, which is recorded as P-CoPt3 / P-CoMoO4.
[0015] In some embodiments of the present invention, in step (1), the nickel foam further includes a pretreatment step before being immersed in the mixed solution, and the pretreatment process is: immersing the nickel foam in a 1-6 mol / L acidic solution, first ultrasonically cleaning it, then cleaning it with anhydrous ethanol and deionized water, and then vacuum drying it.
[0016] In some embodiments of the present invention, the acidic solution is a hydrochloric acid solution.
[0017] In some embodiments of the present invention, the ultrasonic cleaning time is 10-60 min.
[0018] In some embodiments of the present invention, the vacuum drying is carried out at a temperature of 55-65° C. and for a time of 10-15 hours.
[0019] In some embodiments of the present invention, in step (1), the cobalt salt is selected from at least one of cobalt chloride, cobalt nitrate, cobalt sulfate, cobalt oxalate, cobalt acetylacetonate and hydrates of the foregoing substances; preferably cobalt nitrate hexahydrate.
[0020] In some embodiments of the present invention, in step (1), the molybdate is selected from at least one of ammonium molybdate, sodium molybdate and hydrates of the foregoing substances; preferably, it is ammonium molybdate tetrahydrate.
[0021] In some embodiments of the present invention, in step (1), in the mixed solution, the concentration of molybdate is 0.01-0.8 mol / L, the concentration of cobalt salt is 0.01-1 mol / L, and the solvent is water and ethanol in a volume ratio of (0.5-3):1.
[0022] In some embodiments of the present invention, in step (1), the temperature of the hydrothermal reaction is 100-220° C., and the time of the hydrothermal reaction is 4-24 hours.
[0023] In some embodiments of the present invention, in step (2), the phosphorus source is selected from at least one of red phosphorus, sodium hypophosphite, dihydrogen phosphate, hypophosphorous acid, triphenylphosphine and hydrates of the above substances; preferably sodium hypophosphite monohydrate, sodium hypophosphite or sodium hypophosphite monohydrate.
[0024] In some embodiments of the present invention, in step (2), the temperature of the phosphating reaction is 250-450° C., the time of the phosphating reaction is 1-5 hours, and the heating rate is 2-6° C. / min.
[0025] In some embodiments of the present invention, in step (2), the gas flow is nitrogen or argon, and the flow rate of the gas flow is 20-100 cc / min.
[0026] In some embodiments of the present invention, in step (3), the solution containing platinum ions is selected from at least one of hexachloroplatinic acid sodium, platinum tetrachloride, ammonium chloroplatinate, platinum dichloride, potassium chloroplatinate, potassium chloroplatinite, and platinum sulfite.
[0027] In some embodiments of the present invention, in step (3), the concentration of the solution containing platinum ions is 1-15 mg / mL.
[0028] In some embodiments of the present invention, in step (3), the redox reaction time is 0.5-8 hours, preferably 3-5 hours.
[0029] In some embodiments of the present invention, in step (3), after the reduction reaction is completed, the reaction product is further subjected to deionization cleaning and vacuum drying, and the vacuum drying temperature is 50-80° C. and the time is 6-24 hours.
[0030] The third aspect of the present invention provides the use of the above-mentioned hydrogen evolution electrocatalyst in hydrogen production by electrolysis of water.
[0031] In some embodiments of the present invention, when hydrogen is produced by electrolyzing water, the electrolyte is a KOH solution, the hydrogen evolution electrocatalyst is a working electrode, Hg / HgO is a reference electrode, and the graphite rod is a counter electrode.
[0032] In some embodiments of the present invention, the concentration of the KOH solution is 1 mol / L.
[0033] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:
[0034] (1) The active components of the hydrogen evolution electrocatalyst of the present invention are phosphorus-doped cobalt molybdate (P-CoMoO4) and phosphorus-doped CoPt3 (P-CoPt3) with a three-dimensional open nanorod array structure, and P-CoPt3 is anchored on the nanorod array of P-CoMoO4 to form a stable heterostructure. Among them: the nanorod-like structure of P-CoMoO4 is conducive to the transmission of large currents, the anchoring of P-CoPt3 on the nanorod array can avoid the transition aggregation of P-CoPt3, thereby affecting the exposure and utilization of catalytic active sites, and the strong interaction between P-CoPt3 and the P-CoMoO4 carrier can effectively inhibit the dissolution of transition metal cobalt in the catalyst, and can avoid falling off the P-CoPt3 carrier at high current density, thereby significantly improving the catalyst activity and long-term stability.
[0035] (2) The present invention adopts a simple and controllable solution immersion method to generate a P-CoPt3 / P-CoMoO4 heterostructure hydrogen evolution electrocatalyst by in-situ spontaneous redox reaction on the nanorod array. First, a cobalt molybdate nanorod array is grown on the surface of nickel foam, and then the cobalt molybdate rod nanoarray is phosphated under the protection of an inert gas to obtain a P-CoMoO4 nanorod array; then the P-CoMoO4 nanorod array is immersed in a solution containing platinum ions, and a P-CoPt3 / P-CoMoO4 heterostructure nanoarray water electrolysis hydrogen production electrocatalyst is generated in situ by a spontaneous redox reaction. The preparation method is simple, easy to operate, low in cost, and environmentally friendly. The prepared hydrogen heterostructure hydrogen evolution electrocatalyst has the characteristics of high porosity, large surface area, high active site density, low resistance, and nanorod array structure. Therefore, in the water electrolysis hydrogen production reaction at low and high current densities, the hydrogen production heterostructure electrocatalyst prepared by the present invention exhibits the characteristics of sensitive response, high activity, and long-term stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 XRD pattern of P-CoPt3 / P-CoMoO4 prepared in Example 1;
[0037] Figure 2 This is the SEM image of P-CoMoO4 prepared in Example 1;
[0038] Figure 3 This is the SEM image of P-CoPt3 / P-CoMoO4 prepared in Example 1;
[0039] Figure 4 TEM image and mapping image of P-CoPt3 / P-CoMoO4 prepared in Example 1;
[0040] Figure 5 Linear voltammetric scans of the P-CoPt3 / P-CoMoO4 prepared in Example 1 and the hydrogen evolution electrocatalysts of Comparative Examples 1-3 in 1 mol / L KOH electrolyte;
[0041] Figure 6 The P-CoPt3 / P-CoMoO4 prepared in Example 1 was -2 Industrial-grade current density and chronoamperometric curve in 1 mol / L KOH electrolyte;
[0042] Figure 7 The linear voltammetric scanning diagram of P-CoPt3 / P-CoMoO4 prepared in Example 1-3 in 1 mol / L KOH electrolyte;
[0043] Figure 8Linear voltammetric scanning diagrams of P-CoPt3 / P-CoMoO4 prepared in Example 1 and Pt-CoNi-LDH prepared in Comparative Example 4 in 1 mol / L KOH electrolyte;
[0044] Fig. 9 These are the mass activity curves of P-CoPt3 / P-CoMoO4 prepared in Example 1, Pt-CoNi-LDH prepared in Comparative Example 4, and 20wt% Pt / C hydrogen evolution electrocatalyst in Comparative Example 3. DETAILED DESCRIPTION
[0045] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.
[0046] Example 1
[0047] A method for preparing a hydrogen evolution electrocatalyst comprises the following steps:
[0048] (1) Cutting a 1 mm thick nickel foam into a 3 cm × 3 cm square, placing it in 3 mol / L hydrochloric acid, and ultrasonically cleaning it for 30 min to remove the oxide layer on its surface. After the hydrochloric acid treatment, it is immediately cleaned with deionized water and ethanol for 4 times respectively to obtain a pretreated nickel foam;
[0049] (2) Weighing 346 mg of ammonium molybdate tetrahydrate with a purity of 99.9% and 325 mg of cobalt nitrate hexahydrate with a purity of 99.9%, dissolving them in a mixed solution consisting of 10 mL of deionized water and 20 mL of ethanol, and stirring for 15 min to obtain a uniform solution; then adding the nickel foam pretreated in step (1) to the mixed solution, reacting at a temperature of 180° C. for 6 hours to obtain cobalt molybdate grown on the surface of the nickel foam, i.e., CoMoO4·xH2O precursor nanorod array catalyst;
[0050] (3) The CoMoO4·xH2O precursor prepared in step (2) and 2 g of sodium hypophosphite monohydrate are placed in a ceramic boat in a tube furnace, wherein: the sodium hypophosphite monohydrate is located upstream of the gas flow, and the CoMoO4·xH2O precursor is located downstream of the gas flow; the tube furnace is heated to 350°C at a heating rate of 3°C / min, and maintained for 3 hours in an argon environment. After the reaction is completed, it is cooled to room temperature to obtain phosphorus-doped cobalt molybdate, recorded as P-CoMoO4.
[0051] (4) The P-CoMoO4 prepared in step (3) was placed in 20 mL of a 2 mmol / L chloroplatinic acid solution, soaked at 25° C. for 4 hours, then taken out and washed with deionized water and ethanol three times each; then dried in a vacuum drying oven at 60° C. for 12 hours to obtain a heterostructure hydrogen evolution electrocatalyst composed of phosphorus-doped CoPt3 and phosphorus-doped CoMoO4, recorded as P-CoPt3 / P-CoMoO4-4h.
[0052] Example 2
[0053] A method for preparing a hydrogen evolution electrocatalyst comprises the following steps:
[0054] (1) Cutting a 1 mm thick nickel foam into a 4 cm × 3 cm square, placing it in 5 mol / L hydrochloric acid, and ultrasonically cleaning it for 30 min to remove the oxide layer on its surface. After the hydrochloric acid treatment, it is immediately cleaned with deionized water and ethanol for 5 times respectively to obtain a pretreated nickel foam;
[0055] (2) Weighing 415 mg of ammonium molybdate tetrahydrate with a purity of 99.9% and 397 mg of cobalt nitrate hexahydrate with a purity of 99.9%, dissolving them in a mixed solution consisting of 10 mL of deionized water and 20 mL of ethanol, and stirring for 15 min to obtain a uniform solution; then adding the nickel foam pretreated in step (1) to the mixed solution, reacting at a temperature of 150° C. for 8 hours to obtain cobalt molybdate grown on the surface of the nickel foam, i.e., CoMoO4·xH2O precursor nanorod array catalyst;
[0056] (3) The CoMoO4·xH2O precursor prepared in step (2) and 2 g of sodium hypophosphite 8 are placed in a ceramic boat in a tube furnace, wherein: sodium hypophosphite monohydrate is located upstream of the gas flow, and the CoMoO4·xH2O precursor is located downstream of the gas flow; the tube furnace is heated to 450°C at a heating rate of 5°C / min, and maintained for 2.5 hours in an argon environment. After the reaction is completed, it is cooled to room temperature to obtain phosphorus-doped cobalt molybdate, recorded as P-CoMoO4.
[0057] (4) The P-CoMoO4 prepared in step (3) was placed in 20 mL of a 5 mmol / L chloroplatinic acid solution, soaked at 25° C. for 3 hours, then taken out and washed with deionized water and ethanol three times each; then dried in a vacuum drying oven at 70° C. for 10 hours to obtain a heterostructure hydrogen evolution electrocatalyst composed of phosphorus-doped CoPt3 and phosphorus-doped CoMoO4, recorded as P-CoPt3 / P-CoMoO4-3h.
[0058] Example 3
[0059] A method for preparing a hydrogen evolution electrocatalyst comprises the following steps:
[0060] (1) A 1 mm thick nickel foam was cut into a 2.5 cm × 4.5 cm square, placed in 4 mol / L hydrochloric acid, and ultrasonically cleaned for 60 min to remove the oxide layer on the surface. After the hydrochloric acid treatment, it was immediately cleaned with deionized water and ethanol for 3 times respectively to obtain a pretreated nickel foam;
[0061] (2) Weighing 578 mg of ammonium molybdate tetrahydrate with a purity of 99.9% and 552 mg of cobalt nitrate hexahydrate with a purity of 99.9%, dissolving them in a mixed solution consisting of 10 mL of deionized water and 20 mL of ethanol, and stirring for 15 min to obtain a uniform solution; then adding the nickel foam pretreated in step (1) to the mixed solution, reacting at a temperature of 120° C. for 16 hours to obtain cobalt molybdate grown on the surface of the nickel foam, i.e., CoMoO4·xH2O precursor nanorod array catalyst;
[0062] (3) The CoMoO4·xH2O precursor prepared in step (2) and 2 g of sodium hypophosphite monohydrate are placed in a ceramic boat in a tube furnace, wherein: the sodium hypophosphite monohydrate is located upstream of the gas flow, and the CoMoO4·xH2O precursor is located downstream of the gas flow; the tube furnace is heated to 350°C at a heating rate of 3°C / min, and maintained for 3 hours in an argon environment. After the reaction is completed, it is cooled to room temperature to obtain phosphorus-doped cobalt molybdate, recorded as P-CoMoO4.
[0063] (4) The P-CoMoO4 prepared in step (3) was placed in 20 mL of a 3 mmol / L chloroplatinic acid solution, soaked at 25° C. for 5 hours, then taken out and washed with deionized water and ethanol three times each; then dried in a vacuum drying oven at 50° C. for 12 hours to obtain a heterostructure hydrogen evolution electrocatalyst composed of phosphorus-doped CoPt3 and phosphorus-doped CoMoO4, recorded as P-CoPt3 / P-CoMoO4-5h.
[0064] Comparative Example 1
[0065] The P-CoMoO4 prepared in step (3) of Example 1 is used as the hydrogen evolution electrocatalyst of Comparative Example 1.
[0066] Comparative Example 2
[0067] P-CoPt3 is used as the hydrogen evolution electrocatalyst of Comparative Example 2, and its preparation steps are as follows:
[0068] (1) 1.2 mL of chloroplatinic acid solution (0.4 mol / L) and 24 mg of Co(acac)2 were added to 12 mL of ethylene glycol (EG) and mixed to obtain a precursor solution; then 600 mg of KOH and 8 mL of DMF were added to the precursor solution and stirred for about 2 hours, and then the obtained uniform solution was transferred to a reactor and reacted at 160° C. for 12 hours;
[0069] (2) collecting the powder product by centrifugation, then washing it with a mixed solution of deionized water and ethanol, and finally drying it in a vacuum oven at 70°C overnight to obtain CoPt3 powder;
[0070] (3) Sodium hypophosphite monohydrate and CoPt3 powder obtained in step (2) (mass ratio of 1:10) are placed in a ceramic boat in a tubular furnace, wherein: sodium hypophosphite monohydrate is located upstream of the air flow and CoPt3 powder is located downstream of the air flow; heat treatment is performed at 300°C for 2 hours under nitrogen atmosphere protection, and cooling to room temperature to obtain a phosphorus-doped CoPt3 hydrogen evolution electrocatalyst, recorded as P-CoPt3.
[0071] Comparative Example 3
[0072] A commercially available platinum-carbon catalyst Pt / C (Aladdin, Pt loading is 20 wt %) is used as the hydrogen evolution electrocatalyst of Comparative Example 3.
[0073] Comparative Example 4
[0074] Referring to Example 1 of the Chinese invention patent (publication number: CN 118360626 A), a Pt-NiCo-LDH hydrogen evolution electrocatalyst was prepared by electrodeposition, comprising the following steps:
[0075] (1) Weigh 0.2908 g Ni(NO3)2·6H2O and 0.582 g Co(NO3)2·6H2O and dissolve them in 100 mL deionized water and stir at room temperature for 5 min.
[0076] (2) treating the nickel foam (size 1 cm×2 cm) with 3 mol / L hydrochloric acid for 10-12 min, then cleaning it, soaking it with deionized water, ultrasonicating it for 5-7 min, repeating the replacement of deionized water and ultrasonicating it for 3-5 times, and drying it with cold air from a hair dryer;
[0077] (3) Pour 80 mL of the solution in step (1) into a 100 mL electrolytic cell, use the nickel foam in step (2) as the working electrode, the Pt sheet as the counter electrode, and the silver / silver chloride electrode as the reference electrode, and connect them according to the three-electrode system;
[0078] (4) using a constant voltage electrochemical deposition method at a voltage of -1 V for 900 seconds, repeatedly rinsing with deionized water, and drying in a vacuum oven at 60°C for 3 hours;
[0079] (5) Weigh 0.0328 g H2PtCl6 and 11.2212 g KOH and dissolve them in 200 mL deionized water and stir at room temperature for 20 min;
[0080] (6) Pour 80 mL of the solution in step (5) into a 100 mL electrolytic cell, use the sample obtained in step (4) as the working electrode, the carbon rod as the counter electrode, and the mercury / mercury oxide electrode as the reference electrode, and connect them according to the three-electrode system;
[0081] (7) The Pt-NiCo-LDH hydrogen evolution electrocatalyst was prepared by linear cyclic voltammetry at a scan rate of 5 mV / s for 5000 seconds, repeatedly rinsed with deionized water, and dried in a vacuum oven at 60°C for 3 hours.
[0082] Performance Testing
[0083] 1. Composition analysis and microstructure
[0084] Figure 1 The XRD pattern of the hydrogen evolution electrocatalyst prepared in Example 1, Figure 1 The horizontal axis 2θ represents the diffraction angle, and the vertical axis Intensity represents the intensity of the diffraction peak. Figure 1 It can be seen that the unphosphated CoMoO4 and the phosphated P-CoMoO4 are both pure single phases, corresponding to the standard card PDF#-21-0868 of CoMoO4. The P-CoMoO4 prepared in Example 1 undergoes a spontaneous redox reaction after being immersed in a solution containing platinum ions, and a new phase P-CoPt3 is generated, which corresponds to the standard derivative peak PDF#-29-0499 of CoPt3.
[0085] Figure 2 and Figure 3 They are SEM images of P-CoMoO4 and P-CoPt3 / P-CoMoO4 prepared in Example 1 respectively. Figure 2 The microscopic morphology of P-CoMoO4 obtained by phosphating the nanorod arrays uniformly grown in situ on nickel foam. This self-supporting three-dimensional open nanorod array structure is conducive to the exchange of reactive species and the rapid escape of bubbles, especially at high current density, a large number of H2 bubbles will be quickly formed. Figure 3To anchor P-CoPt3 on P-CoMoO4 nanorods, the morphology of P-CoPt3 / P-CoMoO4 heterostructure nanoarray is shown. The nanorod P-CoMoO4 has super hydrophilicity, and the nanorod-like structure is conducive to the rapid transmission of electrons. P-CoPt3 is anchored on the nanorod P-CoMoO4 carrier as the main active site, which is beneficial to improve the utilization of the reaction active sites. It provides a new solution to solve a series of problems such as the rapid release of bubbles generated under industrial-grade current density and the shedding and loss of powdered catalysts.
[0086] Figure 4 TEM image of the P-CoPt3 / P-CoMoO4 heterostructure prepared in Example 1, by HR-TEM ( Figure 4 a and Figure 4 b) and lattice fringes ( Figure 4 c) The analysis confirmed the existence of the heterointerface structure between P-CoPt3 and P-CoMoO4; Figure 4 d and Figure 4 e) and Mapping diagram ( Figure 4 h) It also confirmed that P was successfully doped into CoPt3, which indicates that by immersing P-CoMoO4 in a solution containing platinum ions, P-CoPt3 nanoparticles will be in situ generated (In situ growth) and anchored on P-CoMoO4 to form a highly active and stable heterostructure catalyst.
[0087] The contents of hydrogen evolution electrocatalyst elements in Examples 1-3 and Comparative Examples 1-2 and 4 were tested by ICP-OES. The results are shown in Table 1.
[0088] Table 1:
[0089]
[0090]
[0091] As can be seen from Table 1, the content of precious metal Pt in the hydrogen evolution electrocatalysts prepared in Examples 1-3 of the present invention is relatively low, at 7.9-12.1wt%, which is lower than the Pt content in the platinum carbon catalyst 20wt% Pt / C in Comparative Example 3 and the Pt content in the P-CoPt3 catalyst in Comparative Example 2.
[0092] 2. Electrochemical performance
[0093] In 1 mol / mL KOH electrolyte, the hydrogen evolution electrocatalysts of Examples 1-3 and Comparative Examples 1-4 were used as working electrodes, Hg / HgO was used as a reference electrode, and a graphite rod was used as a counter electrode to test their electrochemical properties.
[0094] The specific experimental process is as follows:
[0095] A 1 mol / mL KOH electrolyte was prepared, and nitrogen was introduced at a rate of 20 mL / min for 20 min to saturate the solution with nitrogen. Then, the hydrogen evolution electrocatalysts of Examples 1-3 and Comparative Examples 1-4 were used as working electrodes, Hg / HgO was used as a reference electrode, and a graphite rod was used as a counter electrode, and connected to an electrochemical workstation. A linear voltammetry test was performed on the electrode material at a scan rate of 5 mV / s. The results are shown in FIG. Figure 5 and Figure 7-9 At 500mAcm -2 The stability of the chronopotentiometry (ET) test was performed at industrial current density. Figure 6 shown.
[0096] Figure 5 The linear voltammetric scan diagram of the P-CoPt3 / P-CoMoO4 prepared in Example 1 and the hydrogen evolution electrocatalysts of Comparative Examples 1-3, Figure 5 The horizontal axis Potential represents voltage, and the vertical axis Current density represents current density. Figure 5 It can be seen that the P-CoPt3 / P-CoMoO4 heterostructure nanorod array hydrogen evolution electrocatalyst prepared in Example 1 is superior to P-CoPt3, P-CoMoO4 and commercial Pt / C in hydrogen evolution performance. -2 and 1000mAcm -2 The overpotentials under current density are 23 mV and 145 mV, respectively, and the electrocatalytic activity is significantly better than that of P-CoPt3 (28 mV, 367 mV), P-CoMoO4 (71 mV, 420 mV) and Pt / C (36 mV, 647 mV). This may be because P-CoPt3 is anchored on the three-dimensional open nanorod array of P-CoMoO4, which is conducive to the full exposure of catalytic active sites. In addition, the strong interaction between metal P-CoPt3 and carrier P-CoMoO4 is also conducive to enhancing the electrocatalytic activity of heterostructured catalysts.
[0097] Figure 6 This is the chronoamperometric curve of P-CoPt3 / P-CoMoO4 prepared in Example 1. Figure 6 The horizontal axis Time represents time, and the vertical axis Potential represents voltage. Figure 6 It can be seen that at 500mAcm -2Under industrial-grade current density conditions, the P-CoPt3 / P-CoMoO4 hydrogen evolution electrocatalyst can operate stably for more than 300 hours with almost no attenuation, which indicates that the P-CoPt3 / P-CoMoO4 heterostructure nanorod array hydrogen evolution electrocatalyst has excellent long-term stability, which is due to the super hydrophilicity of the nanorod P-CoMoO4, which is conducive to the rapid release of H2 generated by the reaction; at the same time, the strong interaction between the metal P-CoPt3 and the carrier P-CoMoO4 synergistically enhances its stability.
[0098] Figure 7 This is the linear voltammetric scan of P-CoPt3 / P-CoMoO4 prepared in Example 1-3 in 1 mol / L KOH electrolyte. Figure 7 The optimal immersion time of P-CoMoO4 in a solution containing platinum ions and the Pt loading suitable for the present invention can be determined from Table 1. When the immersion time is 4 hours, the catalytic activity is the best at 10 and 1000 mA cm -2 The overpotentials under current density are 23mV and 145mV, respectively, which are better than those after immersion for 3 hours (29mV, 215mV) and immersion for 5 hours (27mV, 182mV); and when the Pt content in P-CoPt3 / P-CoMoO4 is 9.7wt%, it has the optimal hydrogen evolution catalytic activity.
[0099] Figure 8 The linear voltammetric scans of P-CoPt3 / P-CoMoO4 prepared in Example 1 and Pt-CoNi-LDH prepared in Comparative Example 4 are shown in FIG. Figure 8 It can be found that P-CoPt3 / P-CoMoO4 has extremely low overpotential and excellent hydrogen evolution performance, and its electrocatalytic hydrogen evolution performance is significantly better than that of Pt-CoNi-LDH. -2 and 300mA cm -2 The overpotentials at different current densities are 23 mV and 142 mV, respectively, which are significantly better than 26 mV and 174 mV of Pt-CoNi-LDH.
[0100] Fig. 9 The mass activity curves of P-CoPt3 / P-CoMoO4 prepared in Example 1, Pt-CoNi-LDH prepared in Comparative Example 4 and 20wt% Pt / C catalyst in Comparative Example 3 are shown in Table 1. Fig. 9 It can be found that P-CoPt3 / P-CoMoO4 has excellent mass activity, which is significantly higher than Pt-CoNi-LDH and commercially available Pt / C.
[0101] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.
Claims
1. A hydrogen evolution electrocatalyst, characterized in that It includes a nickel foam substrate and a catalytically active material loaded on the surface of the nickel foam substrate, wherein the catalytically active material includes phosphorus-doped CoMoO4 and phosphorus-doped CoPt3, wherein the phosphorus-doped CoMoO4 has a three-dimensional open nanorod array structure, the phosphorus-doped CoPt3 is anchored on the nanorod array, and the phosphorus-doped CoMoO4 and phosphorus-doped CoPt3 form a heterostructure.
2. The hydrogen evolution electrocatalyst according to claim 1, characterized in that In the hydrogen evolution electrocatalyst, the loading amount of the catalytically active material is 9-10 mg / cm 2 .
3. The hydrogen evolution electrocatalyst according to claim 1, characterized in that In the catalytically active material, the content of Pt is 5-15wt%, the content of Mo is 30-40wt%, the content of Co is 15-25wt%, and the content of P is 1-5wt%.
4. A method for preparing a hydrogen evolution electrocatalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) immersing the nickel foam in a mixed solution containing molybdate and cobalt salt to perform a hydrothermal reaction, and then washing and drying to obtain cobalt molybdate grown on the surface of the nickel foam; (2) placing the nickel foam with cobalt molybdate grown on the surface obtained in step (1) and a phosphorus source at the downstream and upstream of the airflow in the reaction furnace respectively, heating them to carry out a phosphating reaction, and obtaining a phosphorus-doped cobalt molybdate nanoarray, which is recorded as P-CoMoO4; (3) The P-CoMoO4 is immersed in a solution containing platinum ions, and a redox reaction is carried out at room temperature to generate P-CoPt3 in situ on the surface of P-CoMoO4. After washing and drying, the hydrogen evolution electrocatalyst is obtained, which is recorded as P-CoPt3 / P-CoMoO4.
5. The method for preparing a hydrogen evolution electrocatalyst according to claim 4, characterized in that: In step (1), the nickel foam further includes a pretreatment step before being immersed in the mixed solution, and the pretreatment process is: immersing the nickel foam in a 1-6 mol / L acidic solution, first ultrasonically cleaning, then cleaning with anhydrous ethanol and deionized water, and then vacuum drying.
6. The method for preparing a hydrogen evolution electrocatalyst according to claim 4, characterized in that: In step (1), the cobalt salt is selected from at least one of cobalt chloride, cobalt nitrate, cobalt sulfate, cobalt oxalate, cobalt acetylacetonate and hydrates of the above substances; And / or, the molybdate is selected from at least one of ammonium molybdate, sodium molybdate and hydrates of the above substances; And / or, in the mixed solution, the concentration of molybdate is 0.01-0.8 mol / L, the concentration of cobalt salt is 0.01-1 mol / L, and the solvent is water and ethanol in a volume ratio of (0.5-3):1; And / or, the temperature of the hydrothermal reaction is 100-220° C., and the time of the hydrothermal reaction is 4-24 hours.
7. The method for preparing a hydrogen evolution electrocatalyst according to claim 4, characterized in that: In step (2), the phosphorus source is selected from at least one of red phosphorus, sodium hypophosphite, dihydrogen phosphate, hypophosphorous acid, triphenylphosphine and hydrates of the above substances; And / or, the temperature of the phosphating reaction is 250-450° C., and the time of the phosphating reaction is 1-5 hours; And / or, the gas flow is nitrogen or argon, and the flow rate of the gas flow is 20-100 cc / min.
8. The method for preparing a hydrogen evolution electrocatalyst according to claim 4, characterized in that: In step (3), the solution containing platinum ions is selected from at least one of hexachloroplatinic acid sodium, platinum tetrachloride, ammonium chloroplatinate, platinum dichloride, potassium chloroplatinate, potassium chloroplatinite, and platinum sulfite; And / or, the concentration of the solution containing platinum ions is 1-15 mg / mL.
9. The method for preparing a hydrogen evolution electrocatalyst according to claim 4, characterized in that: In step (3), the redox reaction time is 0.5-8 hours.
10. Use of the hydrogen evolution electrocatalyst according to any one of claims 1 to 3 in hydrogen production by water electrolysis.
Citation Information
Patent Citations
Supported cobalt-platinum superlattice alloy nano particle composite catalyst and preparation method thereof
CN103055893A
Cobalt phosphate and molybdenum trioxide composite nanorod array three-dimensional electrode material and preparation method and application thereof
CN113699552A
Phosphorus-doped porous flaky NiCo2O4 difunctional electrocatalyst as well as preparation and application thereof
CN114438537A
Nano-material with noble metal single atoms dispersed on surface of non-noble metal substrate and preparation method and use of nano-material
WO2023193537A1